Longitudinal characteristics of insight and clinical factors in patients with schizophrenia - Yoshie Sakai; Satsuki Ito; Junya Matsumoto; Yuka Yasuda; Hidenaga Yamamori; Michiko Fujimoto; Naomi Hasegawa; Keiichiro Ishimaru; Kenichiro Miura; Ryota Hashimoto (Wiley, 2023)
Abstract Aims Schizophrenia is a psychiatric disorder presenting a lack of insight. Although insight changes over time, longitudinal studies of insight in schizophrenia are scarce. Furthermore, most previous studies on insight and intelligence have not measured full‐scale IQ and have not been able to examine the relationship between detailed dimensions of cognitive function and insight. In this study, we assessed insight at two time points and assessed dimensions of cognitive function. Methods A total of 163 patients with schizophrenia participated in the study. We evaluated insight at two time points to understand the patterns of change and examined the association between insight and clinical variables. Additionally, we examined the relationship between the dimensions of cognitive function and insight. Results The patients were divided into three groups based on their change in insight over time: stable at a low level of insight (poor insight), stable at a high level of insight (good insight), and changed in insight over time (unstable insight). Those in the poor insight group had lower general intelligence scores than those in the good insight and unstable insight groups. Regarding cognitive function, verbal comprehension was associated with the level of insight at baseline and follow‐up. Regarding psychiatric symptoms, the poor insight group exhibited more severe symptoms than the other two groups, especially regarding positive symptoms. Conclusions Our classification of patients based on changes in insight revealed that poor insight patients had impaired cognitive function, especially verbal comprehension, and more severe positive symptoms than good insight or unstable insight patients.